Dissociation Links Maternal History Of Childhood Abuse To Impaired parenting. Issue 1 (1st January 2022) - Williams, Katharina; Moehler, Eva; Kaess, Michael; Resch, Franz; Fuchs, Anna
ABSTRACT: The present study investigated dissociation as a predictor of parenting and a potential mediator in the relationship between early life maltreatment (ELM) and impaired parenting. Mothers reporting moderate to severe sexual and/or physical abuse (assessed with the Childhood Trauma Questionnaire) formed the maltreatment group (n = 58; MG) and were compared to a non-maltreated comparison group (n = 61; CG) 5 months (T1) and 12 months (T2) postpartum. Dissociative symptoms were assessed with the Dissociative Experiences Scale (DES) at T1. Parenting was investigated by self-report questionnaires and behavior observation (Emotional Availability Scales; EA) at T2. Higher dissociation scores significantly predicted more self-reported parental bonding impairment and stress, higher physical abuse risk and less observed maternal sensitivity, non-intrusiveness and a lower total EA-score during mother–child interactions ( p < .001 to p < .05). Dissociation mediated the associations between ELM and self-reported parenting, but not the associations between ELM and parenting as observed during mother–child interactions. Our results suggest that maternal dissociative symptoms play a distinct role in the intergenerational transmission of adverse childhood experiences and should therefore be targeted in therapeutic interventions provided for victims of physical/sexual childhood abuse and in preventive family programs.